Integrins and ERp57 Coordinate to Regulate Cell Surface Calreticulin in Immunogenic Cell Death - Liu, Chi-Chao; Leclair, Pascal; Pedari, Foujan; Vieira, Heidi; Monajemi, Mahdis; Sly, Laura M.; Reid, Gregor S.; Lim, Chinten James (Frontiers in Oncology, 2019)
Therapy-induced presentation of cell surface calreticulin (CRT) is a pro-phagocytic immunogen beneficial for invoking anti-tumor immunity. Here, we characterized the roles of ERp57 and α-integrins as CRT-interacting proteins that coordinately regulate CRT translocation from the ER to the surface during immunogenic cell death. Using T-lymphoblasts as a genetic cell model, we found that drug-induced surface CRT is dependent on ERp57, while drug-induced surface ERp57 is independent of CRT. Differential subcellular immunostaining assays revealed that ERp57−/− cells have minimal cytosolic CRT, indicating that ERp57 is indispensable for extra-ER accumulation of CRT. Stimulation of integrin activity, with either cell adhesion or molecular agonists, resulted in decreased drug-induced surface CRT and ERp57 levels. Similarly, surface CRT and ERp57 was reduced in cells expressing GFFKR, a conserved α-integrin cytosolic motif that binds CRT. Drug-induced surface ERp57 levels were consistently higher in CRT−/− cells, suggesting integrin inhibition of surface ERp57 is an indirect consequence of α-integrin binding to CRT within the CRT-ERp57 complex. Furthermore, β1−/− cells with reduced expression of multiple α-integrins, exhibit enhanced levels of drug-induced surface CRT and ERp57. Our findings highlight the coordinate involvement of plasma membrane integrins as inhibitors, and ERp57 originating from the ER as promoters, of CRT translocation from the ER to the cell surface.